Multimorbidity as a predictor of mortality in companion dogs - Eric R. Foreman; Laura Corlin; Kate E. Creevy; Jessica M. Hoffman; Joshua M. Akey; Rozalyn M. Anderson; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Matthew D. Dunbar; Virginia R. Fajt; Erica C Jonlin; et al. (GeroScience, 2026)

Reevaluating introduced herbivores in conservation - Jonas Trepel; Robert Buitenwerf; Kristy Ferraro; Elizabeth le Roux; Erick Lundgren; Brian Maitner; Tanya Strydom; Jens‐Christian Svenning; Matthew R. Kerr (Conservation Biology, 2026)

Revisiting Europe's temperate forests: Palaeoecological evidence for an herbivory-driven woodland-grassland mosaic biome - Szymon Czyżewski; Skjold Alsted Søndergaard; Ábel Péter Molnár; Matthew Roy Kerr; Jeppe Aagaard Kristensen; Joe Atkinson; Jonas Trepel; Maciej Sykut; Paweł Radzikowski; Signe Sangill Termansen; Karol Wałach; Elena A. Pearce; et al. (Biological Conservation, 2026)

Climate‐Driven Body Size Changes in Birds and Mammals Reveal Environmental Tolerance Limits - Matthew J. Watson; Jeremy T. Kerr (Global Change Biology, 2025)
Climate change contributes to widespread shifts in body size across taxa which can impact population and community dynamics. However, the reasons for variability in the direction and intensity of responses remain uncertain. Smaller body size improves thermoregulatory efficiency but can increase dehydration risk. Changes in species' body size is likely to balance the tradeoffs of thermoregulation and osmotic balance when responding to shifts in thermal and aridity regimes associated with climate change. Using 119,183 bird and 183,087 mammal body mass, and 15,562 bird and 239,600 mammal body length records, along with species' thermal and aridity limits based on their range geographies, we tested for associations between body size and climatic conditions. We also assessed the impacts of human land use extent and interactions with species thermal environments. We found that smaller body mass measurements across taxa are associated with conditions closer to species' upper thermal (hot) and lower aridity (dry) tolerance limits. Agricultural land use extent was found to be positively associated with body mass measurements for both bird and mammal species. Shorter body lengths were observed for both birds and mammals the closer species were to their upper thermal limits. Further we found that thermal and aridity conditions interacted resulting in stronger negative associations between body mass and hotter temperatures the closer species were to their dry tolerance limits. Our results are consistent with predictions that differences in body size within bird and mammal species are driven by thermoregulatory pressures associated with thermal and aridity regimes. While species' range geographies and phenology are widely known to respond to anthropogenic climate change, the shifts in species' body sizes detected here are a third biotic response that exerts similarly profound ecological, evolutionary, and conservation effects.

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Hydrogeology and Groundwater Flow in a Hummocky Prairie Pothole Complex, Northern Iowa - Keith E. Schilling; Matthew T. Streeter; Phil Kerr; Calvin F. Wolter; Elliot Anderson; Alejandro Gomez; Antonio Arenas-Amado (Wetlands, 2025)

Assessing the effect of multispecies interactions on precautionary reference points using an ensemble modelling approach: A North Sea case study - Michael A. Spence; James A. Martindale; Khatija Alliji; Hayley J. Bannister; Robert B. Thorpe; Nicola D. Walker; Peter J. Mitchell; Matthew R. Kerr; Paul J. Dolder (Fisheries Research, 2024)

Assessing efficacy in MPA design decisions using a bespoke and interactive fisheries management tool - Oliver T. Hogg; Matthew Kerr; Lenka Fronkova; Roi Martinez; William Procter; Lisa Readdy; Christopher Darby (Biological Conservation, 2024)

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Validation of Raman spectroscopic models to verify the origin of Australian beef grown under different production systems - Stephanie M. Fowler; Matthew Kerr; David L. Hopkins; Leigh M. Schmidtke (Meat Science, 2024)

The companion dog as a model for inflammaging: a cross-sectional pilot study - Sarah M. Schmid; Jessica M. Hoffman; Jena Prescott; Holley Ernst; Daniel E. L. Promislow; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; et al. (GeroScience, 2024)

Holocene hydroclimate in highland Costa Rica: new evidence from hydrogen and carbon isotopes in n ‐alkanes of terrestrial leaf waxes in a 10 000‐year sediment profile - Matthew T. Kerr; Sally P. Horn; Chad S. Lane (Journal of Quaternary Science, 2024)
We conducted compound‐specific stable hydrogen (δD) and carbon (δ 13 C) isotope analysis on n ‐alkanes from terrestrial leaf waxes preserved in a 10 000‐year sediment profile from Lago de las Morrenas 1 (9.4925° N, 83.4848° W, 3480 m), a glacial lake on the Chirripó massif of the Cordillera de Talamanca in Costa Rica. Our results demonstrate millennial‐scale variations in hydroclimate across the Holocene, with drier than average conditions in the highlands during the early Holocene, but with gradually increasing precipitation; mesic conditions during the middle Holocene with a gradual drying trend; and highly variable conditions during the late Holocene. This general pattern is punctuated by several centennial‐scale manifestations of global climate events, including dry conditions during the 8200, 5200 and 4200 cal a bp events and the Terminal Classic Drought (1200–850 cal a bp ). Our δ 13 C analyses demonstrate that carbon isotope signals are responding to changes in hydroclimate at the site and reinforce prior interpretations of a stable páramo plant community that established following deglaciation and persisted throughout the Holocene. The shifts in hydroclimate inferred from analyses of n ‐alkanes in Lago de las Morrenas 1 sediments show correspondence with charcoal records in multiple lakes, with fires most common during drier intervals.

A biogeographic–macroecological perspective on the rising novelty of the biosphere in the Anthropocene - Matthew R. Kerr; Alejandro Ordonez; Felix Riede; Jens‐Christian Svenning (Journal of Biogeography, 2024)
The concept of novel ecosystems has been discussed for over more than a decade to describe ecosystems that have an altered species composition and function, such that the community has crossed a threshold forbidding a return to its historical state. While spatial and temporal community compositional change has been well studied in biogeography, studies on novel ecosystems in a modern context are few and tend towards classifying novelty based on a static baseline. Given that the abiotic and biotic drivers of novelty are in a state of rapid change, and reaching levels unprecedented within the last hundred thousand to million years, defining such a threshold requires additional thought. Here, we discuss a biogeographical–macroecological perspective on novel ecosystems, exploring how such a threshold for novelty can be defined in an environment undergoing progressive global change and suggesting pathways through which the emergence and spread of novelty can be further explored, understood and managed.

Linking knowledge and action for climate-ready fisheries: Emerging best practices across the US - Julia G. Mason; Sarah J. Weisberg; Janelle L. Morano; Richard J. Bell; Mark Fitchett; Roger B. Griffis; Elliott L. Hazen; William D. Heyman; Kirstin Holsman; Kristin M. Kleisner; Katie Westfall; Michele K. Conrad; et al. (Marine Policy, 2023)

Enhanced skeletal muscle contractile function and corticospinal excitability precede strength and architectural adaptations during lower-limb resistance training - Matthew T. Wilson; Angus M. Hunter; Malcolm Fairweather; Stewart Kerr; D. Lee Hamilton; Lewis J. Macgregor (European Journal of Applied Physiology, 2023)
Purpose Evolving investigative techniques are providing greater understanding about the early neuromuscular responses to resistance training among novice exercisers. The aim of this study was to investigate the time-course of changes in muscle contractile mechanics, architecture, neuromuscular, and strength adaptation during the first 6-weeks of lower-limb resistance training. Methods Forty participants: 22 intervention (10 males/12 females; 173.48 ± 5.20 cm; 74.01 ± 13.13 kg) completed 6-week resistance training, and 18 control (10 males/8 females; 175.52 ± 7.64 cm; 70.92 ± 12.73 kg) performed no resistance training and maintained their habitual activity. Radial muscle displacement (Dm) assessed via tensiomyography, knee extension maximal voluntary contraction (MVC), voluntary activation (VA), corticospinal excitability and inhibition via transcranial magnetic stimulation, motor unit (MU) firing rate, and muscle thickness and pennation angle via ultrasonography were assessed before and after 2, 4, and 6-weeks of dynamic lower-limb resistance training or control. Results After 2-weeks training, Dm reduced by 19–25% in the intervention group; this was before any changes in neural or morphological measures. After 4-weeks training, MVC increased by 15% along with corticospinal excitability by 16%; however, there was no change in VA, corticospinal inhibition, or MU firing rate. After 6-weeks training there was further MVC increase by 6% along with muscle thickness by 13–16% and pennation angle by 13–14%. Conclusion Enhanced contractile properties and corticospinal excitability occurred before any muscle architecture, neural, and strength adaptation. Later increases in muscular strength can be accounted for by architectural adaptation.

Greenness modifies the association between ambient air pollution and cognitive function in Australian adolescents, but not in mid-life adults - Yichao Wang; Mallery Crowe; Luke D. Knibbs; Matthew Fuller-Tyszkiewicz; Lærke Mygind; Jessica A. Kerr; Melissa Wake; Craig A. Olsson; Peter G. Enticott; Rachel L. Peters; Galina Daraganova; Suzanne Mavoa; et al. (Environmental Pollution, 2023)

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

Banking on a new understanding: translational opportunities from veterinary biobanks - D. LaLonde-Paul; L. Mouttham; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; Virginia R. Fajt; Annette L. Fitzpatrick; Unity Jeffery; et al. (GeroScience, 2023)

Once-daily feeding is associated with better health in companion dogs: results from the Dog Aging Project - Emily E. Bray; Zihan Zheng; M. Katherine Tolbert; Brianah M. McCoy; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; et al. (GeroScience, 2022)

Stable isotope analysis of vegetation history and land use change at Laguna Santa Elena in southern Pacific Costa Rica - Matthew T. Kerr; Sally P. Horn; Chad S. Lane (Vegetation History and Archaeobotany, 2020)

Colistin causes profound morphological alteration but minimal cytoplasmic membrane perforation in populations of Escherichia coli and Pseudomonas aeruginosa - Noëlle H. O’Driscoll; T. P. Tim Cushnie; Kerr H. Matthews; Andrew J. Lamb (Archives of Microbiology, 2018)

Computation of the inverse additive relationship matrix for autopolyploid and multiple-ploidy populations - Matthew G. Hamilton; Richard J. Kerr (Theoretical and Applied Genetics, 2018)

A new eimerian (Apicomplexa: Eimeriidae), from ornate box turtle, Terrapene ornata (Agassiz) (Testudines: Emydidae) from northwest Arkansas, USA - Chris T. McAllister; Dagmara Motriuk-Smith; Catherine M. Kerr; Kristine N. Carmen; R. Scott Seville; Matthew B. Connior (Systematic Parasitology, 2017)

Dexamphetamine effects on prepulse inhibition (PPI) and startle in healthy volunteers - Kate Chitty; Matthew A. Albrecht; Kyran Graham; Chantelle Kerr; Joseph W. Y. Lee; Rajan Iyyalol; Mathew T. Martin-Iverson (Psychopharmacology, 2014)

Potassium Loss from Chlorhexidine-Treated Bacterial Pathogens is Time- and Concentration-Dependent and Variable Between Species - Noelle H. O’Driscoll; Olga Labovitiadi; T. P. Tim Cushnie; Kerr H. Matthews; Andrew J. Lamb (Current Microbiology, 2014)

Pseudo-Continuous Arterial Spin Labelling MRI for Non-Invasive, Whole-Brain, Serial Quantification of Cerebral Blood Flow Following Aneurysmal Subarachnoid Haemorrhage - Michael E. Kelly; Matthew J. Rowland; Thomas W. Okell; Michael A. Chappell; Rufus Corkill; Richard S. Kerr; Jon Westbrook; Peter Jezzard; Kyle T. S. Pattinson (Translational Stroke Research, 2013)

Production and Evaluation of an Antimicrobial Peptide-Containing Wafer Formulation for Topical Application - Noelle H. O’Driscoll; Olga Labovitiadi; T. P. Tim Cushnie; Kerr H. Matthews; Derry K. Mercer; Andrew J. Lamb (Current Microbiology, 2013)

Genetic variation in PARL influences mitochondrial content - Joanne E. Curran; Jeremy B. M. Jowett; Lawrence J. Abraham; Luke A. Diepeveen; Katherine S. Elliott; Thomas D. Dyer; Lyndal J. Kerr-Bayles; Matthew P. Johnson; Anthony G. Comuzzie; Eric K. Moses; Ken R. Walder; Gregory R. Collier; et al. (Human Genetics, 2010)

Bordetella pertussis Infection: Pathogenesis, Diagnosis, Management, and the Role of Protective Immunity - J. R. Kerr; R. C. Matthews (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Semiquantitative Polymerase Chain Reaction Enzyme Immunoassay for the Diagnosis of Pertussis - R. C. Matthews; N. Golbang; W. M. Brück; D. Owen; A. Bailey; V. Weston; J. R. Kerr (European Journal of Clinical Microbiology & Infectious Diseases, 1999)